Effect of the number of blades and solidity on the performance of a vertical axis wind turbine - Delafin, Pierre-Luc; Nishino, Takafumi; Wang, Lin; Kolios, Athanasios (IOP Publishing, 2016)
Two, three and four bladed phgr-shape Vertical Axis Wind Turbines are simulated using a free-wake vortex model. Two versions of the three and four bladed turbines are considered, one having the same chord length as the two-bladed turbine and the other having the same solidity as the two-bladed turbine. Results of the two-bladed turbine are validated against published experimental data of power coefficient and instantaneous torque. The effect of solidity on the power coefficient is presented and the instantaneous torque, thrust and lateral force of the two-, three- and four-bladed turbines are compared for the same solidity. It is found that increasing the number of blades from two to three significantly reduces the torque, thrust and lateral force ripples. Adding a fourth blade further reduces the ripples except for the torque at low tip speed ratio. This work aims to help choosing the number of blades during the design phase of a vertical axis wind turbine.